Differentially induced immunity in buccal and nasal mucosae after vaccination for SARS–CoV–2: Prospects for mass scale immunity-screening in large populations - Tsamadou, Chrysanthi; Ludwig, Carolin; Scholz, Judith; Proffen, Matthias; Hägele, Janina; Rode, Immanuel; Körper, Sixten; Fabricius, Dorit; Jahrsdörfer, Bernd; Neuchel, Christine; Amann, Elisa; Schrezenmeier, Hubert; et al. (Frontiers in Immunology, 2022)
Introduction Humoral immunity after SARS-CoV-2 vaccination has been extensively investigated in blood. Aim of this study was to develop an ELISA method in order to determine the prevalence of IgG and IgA SARS-CoV-2 domain 1 spike-protein (S) specific antibodies (Abs) in buccal and nasal mucosal surfaces of vaccinees. Methods To this end, we analyzed 69 individuals who received their first vaccine dose between February and July 2021. Vaccines administered were BNT162b2, mRNA-1273 or ChAdOx1-nCoV-19. Detection of IgG and IgA Abs was performed using commercial ELISA kits for both blood and swab samples after protocol modification for the latter. Results Anti-spike IgG and IgA Abs in the buccal and/or nasal swabs were detectable in >81% of the study subjects after the second dose. The IgG measurements in buccal swabs appeared to correlate in a more consistent way with the respective measurements in blood with a correlation coefficient of r=0.74. It is of note that IgA Abs appeared to be significantly more prevalent in the nasal compared to the buccal mucosa. Optimal selection of the assay cut-off for the IgG antibody detection in buccal swabs conferred a sensitivity of 91.8% and a specificity of 100%. Last, individuals vaccinated with mRNA-based vaccines exhibited higher antibody levels in both blood and mucosal surfaces compared to those receiving ChAdOx1-nCoV-19 confirming previously reported results. Conclusion In conclusion, our findings show a differential prevalence of anti-S Abs on mucosal surfaces after vaccination for SARS-CoV-2, while they also set the basis for potential future use of IgG antibody detection in buccal swabs for extended immunity screening in large populations.